Fecal transplantation for ulcerative colitis: current evidence and future applications. (2nd April 2020) - Lopetuso, Loris R.; Ianiro, Gianluca; Allegretti, Jessica R.; Bibbò, Stefano; Gasbarrini, Antonio; Scaldaferri, Franco; Cammarota, Giovanni
ABSTRACT: Introduction : Established evidence suggests that gut microbiota plays a role in ulcerative colitis (UC). Fecal microbiota transplantation (FMT) is clearly recognized as a highly effective treatment for patients with recurrent Clostridium difficile infection and has been investigated also in patients with UC, with promising results. Areas covered : Literature review was performed to select publications concerning current evidence on the role of gut microbiota in the pathogenesis of UC, and on the effectiveness of FMT in this disorder. Expert opinion : The randomized controlled trials published investigating the use of FMT suggested a potential role for FMT in the treatment of mild to moderate UC. However, given several unanswered questions regarding donor selection, dose, route of administration and duration of therapy, this is not yet recommended as a viable therapy option. FMT has allowed for more in depth investigation with regards to the role the gut microbiota may be playing in UC. This knowledge is critical to identifying where FMT may appropriately fit in the UC treatment paradigm. As our understanding of the role the microbiome plays in this chronic disease, FMT, and then eventually defined microbes, will hopefully serve in a complementary role to conventional IBD therapies.